Single‐cell RNA sequencing profiling in a patient with discordant primary cutaneous B‐cell and T‐cell lymphoma reveals micromilieu‐driven immune skewing. (1st November 2021) - Jonak, C.; Alkon, N.; Rindler, K.; Rojahn, T.B.; Shaw, L.E.; Porkert, S.; Weninger, W.; Trautinger, F.; Stingl, G.; Tschandl, P.; Cerroni, L.; Farlik, M.; et al.
Summary: Background: Primary cutaneous lymphomas comprise a heterogeneous group of B‐cell and T‐cell malignancies which often show an indolent course, but can progress to aggressive disease in a subset of patients. Diagnosis is often delayed owing to clinical and histopathological similarities with benign inflammatory conditions. Especially during early disease, cancer cells are present at relatively low percentages compared with the inflammatory infiltrate, an interplay that is currently only insufficiently understood. Objectives: To improve diagnostics and perform molecular characterization of a complex type of primary cutaneous lymphoma. Methods: Single‐cell RNA sequencing (scRNA‐seq) was performed and combined with T‐cell and B‐cell receptor sequencing. Results: We were able to diagnose a patient with concurrent mycosis fungoides (MF) and primary cutaneous follicle centre lymphoma (PCFCL), appearing in mutually exclusive skin lesions. Profiling of tumour cells and the tissue microenvironment revealed a type‐2 immune skewing in MF, most likely guided by the expanded clone that also harboured upregulation of numerous pro‐oncogenic genes. By contrast, PCFCL lesions exhibited a more type‐1 immune phenotype, consistent with its indolent behaviour. Conclusions: These data not only illustrate the diagnostic potential of scRNA‐seq, but also allow the characterization of specific clonal populations that shape the unique tissue microenvironment in clinically distinct types of lymphoma skin lesions.